Pengaruh Pengemasan terhadap Mutu Pinekuhe Layang (Decapterus Sp) Asap (Packaging Influence of Smoked Pinekuhe Fish) - Jefri A. Mandeno; Mukhlis A. Kaim (Jurnal Ilmiah Tindalung, 2015)
The aim of this research is to determine the influence of packaging to pinekuhe fish quality, Compare of packaged pinekuhe fish and unpackaged pinekuhe fish and also find out the interested of consumer with packaged pinekuhe fish and unpackaged pinekuhe fish. The conclusion of this research show that the pinekuhe fish was packaged by plastic in vacuum conditions is better than pinekuhe fish was packaged by plastic in unvacuum conditions and unpackaged pinekuhe fish. Total Plate Count and organoleptic analysis show that the packaged pinekuhe fish has a better quality than unpackaged pinekuhe fish. Spoiled was show in six day storage of pinekuhe fish.